Phenol degradation and molecular analysis of phenol hydroxylase from Pseudomonas cedrina - Tengku Kamrul, Tengku Nur Saleha (2015)
Phenols are toxic aromatic compounds that act as serious environmental pollutants especially in industrial wastewater. These phenolic compounds are harmful towards living organisms and can lead to serious health problems if the sources of phenol pollution are not being treated immediately. Thus, bioremediation process using microorganisms is a preferable method to remove phenol since the process is cheaper, effective and forms non-toxic end products. In this study, an aerobic fluorescent bacterium, Pseudomonas cedrina was successfully shown its potential ability to degrade phenol and utilise it as its sole source of carbon since it can degrade phenol concentration ranging from 0.1 to 1.0 g/L. Furthermore, the highest phenol removal rate of P. cedrina was at 0.3 g/L. Phenol hydroxylase, an enzyme that helps to degrade phenol into catechol, was amplified using specific primers at optimum temperature of 50.7ᵒC. Besides that, DNA sequencing result has revealed that the size of DNA sequence of putative phenol hydroxylase is 1166 bp. However, BLAST algorithm results have shown negative results that phenol hydroxylase gene was not identified in P. cedrina. Therefore, several recommendation involving molecular genetic studies are emphasised for future work research.